Pancreatic cancer risk in hereditary pancreatitis - Weiss, Frank U. (Frontiers in Physiology, 2014)
Inflammation is part of the body’s immune response in order to remove harmful stimuli – like pathogens, irritants or damaged cells - and start the healing process. Recurrent or chronic inflammation on the other side seems a predisposing factor for carcinogenesis and has been found associated with cancer development. In chronic pancreatitis mutations of the cationic trypsinogen (PRSS1) gene have been identified as risk factors of the disease. Hereditary pancreatitis is a rare cause of chronic pancreatic inflammation with an early onset, mostly during childhood. Hereditary pancreatitis often starts with recurrent episodes of acute pancreatitis and the clinical phenotype is not very much different from other etiologies of the disease. The long-lasting inflammation however generates a tumor promoting environment and represents a major risk factor for tumor development This review will reflect our knowledge concerning the specific risk of hereditary pancreatitis patients to develop pancreatic cancer.